FAKTOR-FAKTOR STRATEGI PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PEGADAIAN SYARIAH CABANG BLANGPIDIE - Raudhatun Nadiyah; Hamdi Harmen; Ivon Jalil; Rusdi, Rusdi (Nusantara Hasana Journal, 2025)
This study aims to examine the factors of promotional strategy, service quality on customer satisfaction of Pegadaian Syariah Blangpidie Branch. The population in this study were all objects that had certain characteristics that had used products and services at Pegadaian Syariah Blangpidie Branch and who had used products or services at Pegadaian Syariah Blangpidie Branch at least 1 time. Sample selection using purposive sampling method, and obtained 96 customers. The method used in this study is quantitative method. The tests used include data analysis methods (validity test, reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple regression analysis test t test, f test, R2 determination test), assisted by spss version.25program. The study indicate that partially the promotional strategy has a positive and significant effect on customer satisfaction of Pegadaian Syariah Blangpidie Branch. And partially the quality of service has a positive and significant effect on customer satisfaction of Pegadaian Syariah Blangpidie Branch. Based on the results of the f test analysis, the promotion strategy and service quality together have a positiveand significant impact on the level of customer satisfaction at the Blangpidie Branch Syariah pawnshop.